2018
DOI: 10.14814/phy2.13650
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant treatment in patients with peripheral artery disease

Abstract: Peripheral artery disease is an atherosclerotic disease of arterial vessels that mostly affects arteries of lower extremities. Effort induced cycles of ischemia and reperfusion lead to increased reactive oxygen species production by mitochondria. Therefore, the pathophysiology of peripheral artery disease is a consequence of metabolic myopathy, and oxidative stress is the putative major operating mechanism behind the structural and metabolic changes that occur in muscle. In this review, we discuss the evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 108 publications
(203 reference statements)
1
36
0
Order By: Relevance
“…5 However, the results of clinical studies regarding potential effects of antioxidant administration are disappointing, questioning the relevance of the preclinical hind limb ischaemia models in other situations. 5,6 Conversely, recent studies revealed that some pharmacological targets remain effective even in the presence of hypercholesterolaemia. 19 Thus, pharmacological inhibition of GSK3b allowed muscle protection in both normal and hypercholesterolaemic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, the results of clinical studies regarding potential effects of antioxidant administration are disappointing, questioning the relevance of the preclinical hind limb ischaemia models in other situations. 5,6 Conversely, recent studies revealed that some pharmacological targets remain effective even in the presence of hypercholesterolaemia. 19 Thus, pharmacological inhibition of GSK3b allowed muscle protection in both normal and hypercholesterolaemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Such antioxidant strategies have thus been considered as promising therapeutic targets, but clinical results have been mostly disappointing and antioxidant therapies are still far from being integrated into treatment algorithms for peripheral arterial disease, despite promising preclinical efficacy. 1,5,6 This discrepancy has brought into question the relevance of the preclinical hind limb ischaemia models that were used for efficacy testing. 7 Thus, although this CLI model can be considered to be relevant to CLI, it does not entirely reproduce the complex human condition and there are important limitations that should be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some progress in studying the possibility of enhancing the antioxidant properties of albumin, the development of the methods for correcting oxidative stress taking into account this ability of the protein is still in its infancy. Recently, such classes of compounds as thiol antioxidants ( n -acetylcysteine, carbocysteine and erdosteine), superoxide dismutase mimetics (magnesium-containing porphyrins), NADPH oxidase inhibitors (apocinin, diphenyliod), setanaxib traps (disulfenton sodium), activators of the transcription factor Nrf2 (Sulforaphane, Bardoxelone methyl, Dimethylfumarate) have been actively tested or are already being used to reduce oxidative stress [ 168 , 169 , 170 , 171 ]. It might be that in the future it will be possible to create the complex therapy for oxidative stress management taking into account the functional properties of albumin.…”
Section: Antioxidant Properties Of Albumin: Practical Applicationmentioning
confidence: 99%
“…FMD is believed to be mediated by NO [ 13 ]. We have recently reviewed the evidence for elevated oxidative stress in PAD, as well as the interplay between NO and oxidative stress [ 19 ]. High levels of ROS can lead to the rapid inactivation of NO to form peroxynitrite, thus reducing the amount of bioactive NO [ 20 ].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%